2014
DOI: 10.1631/jzus.b1300320
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.)

Abstract: Abstract:1-Aminocyclopropane-1-carboxylic acid synthase (ACS) and 1-aminocyclopropane-1-carboxylic acid oxidase (ACO) are encoded by multigene families and are involved in fruit ripening by catalyzing the production of ethylene throughout the development of fruit. However, there are no reports on ACS or ACO genes in mulberry, partly because of the limited molecular research background. In this study, we have obtained five ACS gene sequences and two ACO gene sequences from Morus Genome Database. Sequence alignm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Five MaACS and two MaACO genes involved in ethylene biosynthesis in Morus have been reported by our previous research [ 27 ]. In this study, we identified 11 putative ethylene signaling genes in M .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five MaACS and two MaACO genes involved in ethylene biosynthesis in Morus have been reported by our previous research [ 27 ]. In this study, we identified 11 putative ethylene signaling genes in M .…”
Section: Resultsmentioning
confidence: 99%
“…4 ). Our previous study suggested that MaACO2 and MaACS3 showed rapid increases in expression throughout fruit development and were upregulated by ethephon in the fruit at 20 DAF, which may be attributed to the production of ethylene during the fruit transitional period [ 27 ]. Therefore, fruit at 26 DAF may represent the transition stage from system I ethylene production to system II ethylene production, and the respiration rate during fruit development also supports this suggestion ( S1 Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mulberry adapts well to drought, salinity, water logging, and other abiotic stress conditions, but little is known regarding the molecular mechanisms of the tolerance. In our previous studies, the elements involved in mulberry ethylene biosynthesis and signal transduction were identified and its functions in fruit development were clarified (Liu et al, 2014;Liu et al, 2015). However, the functions of mulberry ethylene biosynthesis and signal pathway related genes in other aspects of the lifecycle remain unclear, PeerJ reviewing PDF | (2018:10:31930:1:0:NEW 27 Dec 2018)…”
Section: Mulberry (Morus L) Is An Economically Important Perennial Wmentioning
confidence: 99%
“…As part of our systematic research on chitosan, we have paid more attention to the unique dissolving capacity of amino acid IL . It has been found that the aqueous solution of [Gly]Cl IL can afford adequate dissolvability for chitosan, sequentially the film forming, fiber forming, and degradation process on this platform can be conducted successfully.…”
Section: Introductionmentioning
confidence: 99%